Multiobjective nonfragile fuzzy control for nonlinear stochastic financial systems with mixed time delays - Yang, Yang; Xia, Jianwei; Zhao, Jianli; Li, Xiaodi; Wang, Zhen (Nonlinear Analysis: Modelling and Control, 2019)
In this study, a multiobjective nonfragile control is proposed for a class of stochastic Takagi and Sugeno (T–S) fuzzy systems with mixed time delays to guarantee the optimal H2 and H∞ performance simultaneously. Firstly, based on the T–S fuzzy model, two form of nonfragile state feedback controllers are designed to stabilize the T–S fuzzy system, that is to say, nonfragile state feedback controllers minimize the H2 and H∞ performance simultaneously. Then, by applying T–S fuzzy approach, the multiobjective H2/H∞ nonfragile fuzzy control problem is transformed into linear matrix inequality (LMI)-constrained multiobjective problem (MOP). In addition, we efficiently solve Pareto optimal solutions for the MOP by employing LMI-based multiobjective evolution algorithm (MOEA). Finally, the validity of this approach is illustrated by a realistic design example.
Keywords: multiobjective nonfragile control; mixed time delays; Pareto optimal solutions; linear matrix inequality